Mesophase pitch carbon fiber and preparation method thereof

By adding carbon nanotubes or graphene to the mesophase bitumen and preparing the raw silk by using melt electrospinning process, the problem of difficulty in spinning pure mesophase bitumen carbon fibers in the prior art was solved, and high-oriented ultrafine mesophase bitumen carbon fibers were successfully prepared, with better performance.

CN119800556AActive Publication Date: 2025-04-11CHINA SHENHUA COAL TO LIQUID & CHEM CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510004749.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-11
Estimated Expiration
2045-01-02

AI Technical Summary

Technical Problem

The prior art is difficult to spin pure mesophase asphalt carbon fibers by solution electrospinning method, and the method of electrospinning in a melted state has not been reported.

Method used

0.1-0.3 wt.% carbon nanotubes or graphene were added to the molten mesophase bitumen, the raw wire was prepared by melt electrospinning process, and nanoscale ultrafine mesophase bitumen carbon fibers were prepared by preoxidation and carbonization.

Benefits of technology

By adding carbon nanotubes or graphene, the conductivity and spinning properties of mesophase bitumen are improved, and high-oriented ultrafine mesophase bitumen carbon fibers with diameters of 150-280 nanometers were successfully prepared, with better performance than conventional micron-scale carbon fibers.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a mesophase pitch carbon fiber and a preparation method thereof, and the method comprises the following steps: 1) adding 0.1-0.3 wt.% of carbon nanotube or graphene into molten mesophase pitch to obtain a compound; 2) carrying out melt spinning on the compound at 295-360 DEG C by adopting a melt electrostatic spinning process to obtain a precursor; and 3) pre-oxidizing and carbonizing the precursor to prepare the mesophase pitch carbon fiber. By adding a small amount of carbon nanotubes or graphene, the spinnability of melt electrostatic spinning of the mesophase pitch can be improved, the axial orientation of carbon atoms can be enhanced, and the prepared carbon fiber has better performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of carbon fiber preparation, and in particular to a mesophase pitch carbon fiber and a preparation method thereof. Background Art

[0002] Carbon fiber is an inorganic non-metallic reinforcing fiber with high strength, high modulus and low density. It is mainly used as a reinforcing agent and functional additive in the manufacture of composite materials. Mesophase pitch carbon fiber is an important variety of carbon fiber. It has a higher modulus and better thermal conductivity, and has an irreplaceable position in aerospace and satellites. At present, the diameter of carbon fiber products is about 10 microns, which is the mainstream of products. Electrospinning is a new spinning method developed in recent years. Under high-voltage electrostatic drawing, fibers of several hundred nanometers can be spun, and it has been applied to the spinning of various ultra-fine carbon fibers. Electrospinning is divided into two methods: solution spinning and melt spinning. Solution electrospinning is to dissolve the material in a solvent. The parameters are simple to adjust and it is the current mainstream method. However, the premise of solution electrospinning is that the material can be dissolved in the relevant solvent.

[0003] Mesophase asphalt is a liquid crystal-like macromolecular substance. Currently, there is no solvent that can completely dissolve it. Therefore, the current electrospinning of asphalt solutions involves electrospinning asphalt as an additive together with other materials. For example, He Yiting prepared nano-scale carbon fibers by co-spinning asphalt and polyacrylonitrile in "Preparation and Capacitive Properties of Asphalt / Polyacrylonitrile Composite Nanocarbon Fiber Nonwoven Fabrics" ("New Carbon Materials", 2021, 36(1)227-234.). However, electrospinning of a solution of pure spinning asphalt cannot be achieved. However, there are no reports on directly electrospinning spinning asphalt in a molten state to prepare raw fibers, and then obtaining ultrafine asphalt carbon fibers with better performance. Summary of the invention

[0004] In order to solve the above defects in the prior art, the present invention provides a mesophase pitch carbon fiber and a preparation method thereof, which directly electrospins the mesophase pitch in a molten state to prepare a precursor, and then post-processes it to prepare a nano-scale ultrafine pitch carbon fiber.

[0005] To achieve the above-mentioned object of the invention, the first aspect of the present invention provides a method for preparing mesophase pitch carbon fiber, comprising:

[0006] 1) adding 0.1-0.3 wt.% of carbon nanotubes or graphene to molten mesophase pitch to obtain a composite;

[0007] 2) melt spinning the composite at 295-360° C. using a melt electrospinning process to obtain a raw fiber;

[0008] 3) The raw silk is pre-oxidized and carbonized to prepare the intermediate phase pitch carbon fiber.

[0009] In the above technical solution of the present invention, mesophase pitch is used as raw material, and ultrafine mesophase pitch precursor is prepared by melt electrostatic spinning, and mesophase pitch ultrafine carbon fiber is obtained after treatment. Among them, the molten mesophase pitch has poor conductivity and insufficient charge carrying capacity, which often leads to instability or even failure of melt electrostatic spinning; to solve this problem, the present application adds 0.1-0.3wt.% of carbon nanotubes or graphene to the molten mesophase pitch. Carbon nanotubes and graphene are two highly oriented carbon materials with good conductivity. As additives of mesophase pitch, they can improve the charging ability and have the function of guiding the orientation of mesophase pitch in the process of forming fibers. Therefore, the present invention can improve the spinnability of mesophase pitch melt electrostatic spinning and enhance the orientation of carbon atoms along the axial direction by adding a small amount of carbon nanotubes or graphene, so that the prepared carbon fiber has better performance.

[0010] Further, the softening point of the mesophase pitch in step 1) is 260-320°C, exemplarily 263°C, 265°C, 268°C, 270°C, 272°C, 275°C, 278°C, 280°C, 283°C, 285°C, 288°C, 290°C, 293°C, 295°C, 298°C, 300°C, 305°C, 308°C, 310°C, 312°C, 315°C, 318°C, etc. The above softening point range can ensure that the mesophase content of the pitch is greater than 85%, and the mesophase pitch has sufficient fluidity to ensure that it is still spinnable after adding carbon nanotubes or graphene, and makes the spinning temperature suitable and easy to operate. In the present invention, the spinning temperature is exemplarily 298°C, 300°C, 305°C,

[0011] 310°C, 315°C, 320°C, 325°C, 330°C, 335°C, 340°C, 345°C, 350°C, 355°C, etc. The amount of carbon nanotubes or graphene added is exemplarily: 0.12wt.%, 0.15wt.%, 0.18wt.%, 0.20wt.%, 0.22wt.%, 0.25wt.%, 0.28wt.%, etc.

[0012] Furthermore, the carbon nanotubes in step 1) are less than 30 nanometers in length and 20-50 nanometers in diameter. The above size range can ensure that the carbon nanotubes have a good effect in assisting the orientation of carbon fibers, while preventing negative effects such as loss of spinnability due to excessive increase in softening point caused by addition and uneven mixing of carbon nanotubes with the intermediate phase asphalt due to excessive size. The length of the carbon nanotubes is preferably 1-5 microns.

[0013] Furthermore, the length and width of the graphene in step 1) are 15-30 nanometers. Selecting the above size range can ensure that the graphene has a good effect in assisting the orientation of carbon fibers, while preventing negative effects such as loss of spinnability due to excessive increase in the softening point caused by addition, and uneven mixing of the graphene with the intermediate phase asphalt due to its excessive size.

[0014] Furthermore, the mesophase asphalt in step 1) is an asphalt comprising a mesophase content of 85% (volume fraction) or more, preferably a mesophase content of 90% or more.

[0015] Furthermore, the molten mesophase asphalt in step 1) is prepared by heating the mesophase asphalt to a temperature above the softening point to melt the mesophase asphalt into a flowable liquid.

[0016] Furthermore, the adding process in step 1) is carried out under stirring, preferably at a stirring speed of 200-300 rpm and a stirring time of 20-30 minutes.

[0017] Furthermore, the pre-oxidation process in step 3) is to use an oxidant to molecularly cross-link the precursor fibers, the oxidation temperature is 220-330° C., and the oxidation time is 2-4 hours. The oxidant is preferably air.

[0018] Furthermore, the carbonization process parameters in step 3) include treatment at 1000-1300° C. for 0.5-5 hours under nitrogen protection.

[0019] Furthermore, in steps 1)-3), considering the intermediate phase ratio of the intermediate phase asphalt, the influence of carbon nanotubes or graphene on the softening point of the intermediate phase asphalt, and the effect of carbon nanotubes or graphene on the assisted orientation, further preferred parameters include: the addition amount of carbon nanotubes or graphene is 0.15-0.25wt.%, the spinning temperature is 320-340°C, the softening point of the intermediate phase asphalt is 270-295°C, the intermediate phase asphalt softening point is less than 270 degrees, the intermediate phase asphalt content will be less, affecting the strength of the fiber; the intermediate phase softening point exceeds 295 degrees, the viscosity increases after melting, and the spinning temperature needs to be increased, which will affect the quality of the intermediate phase asphalt and put higher requirements on the equipment.

[0020] The present invention obtains the above-mentioned feasible preparation method through process exploration, wherein the structure and softening point of the mesophase pitch, the morphology of carbon nanotubes or graphene, and the amount of addition have an impact on the final carbon fiber performance. Mesophase pitch carbon fiber is composed of graphite crystals that are highly oriented along the axial direction. The higher the orientation, the better the carbon fiber performance. The mesophase pitch with a large fusion structure is a high-quality raw material for converting ideal graphite crystals, and the mesophase content in the pitch is preferably above 90%. Since carbon nanotubes and graphene are highly oriented carbon materials, their addition promotes the orientation of the final carbon fiber. The more perfect the structure of the carbon nanotubes or graphene, the better the orientation, the greater the orientation effect on the carbon fiber. Further, the size of the carbon nanotubes and graphene is limited to a certain range, which ensures that their orientation is excellent and prevents the difficulty of mixing due to excessive size. Moreover, since they are solid substances, the fluidity of the mesophase pitch will be reduced after addition, which has a negative impact on the spinning performance of the mesophase pitch, so it is necessary to control the amount of addition.

[0021] The second aspect of the present invention provides mesophase pitch carbon fibers prepared by the above method, wherein the diameter of the mesophase pitch carbon fibers is 150-280 nanometers.

[0022] Compared with the prior art, the present invention has the following advantages:

[0023] The present invention provides a method for preparing ultrafine mesophase pitch carbon fiber, by adding carbon nanotubes or graphene to molten mesophase pitch, adopting a melt electrostatic spinning process to prepare ultrafine mesophase pitch precursor, and obtaining ultrafine mesophase pitch carbon fiber through post-treatment of pre-oxidation and carbonization, wherein the diameter of the mesophase pitch carbon fiber is 150-280 nanometers. The finer the diameter of the carbon fiber, the higher the orientation of carbon atoms along the axial direction of the fiber, and the better various properties. Therefore, the present invention overcomes the difficulty that pure mesophase pitch cannot be spun by solution electrostatic spinning. The ultrafine carbon fiber prepared after adding carbon nanotubes or graphene has good orientation, resulting in better mechanical properties and electrical and thermal conductivity.

[0024] Other features and advantages of the present invention will be described in detail through the following detailed description. DETAILED DESCRIPTION

[0025] The following will clearly and completely describe the concept of the present application and the technical effects produced in combination with the embodiments, so as to fully understand the purpose, features and effects of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of them. Based on the embodiments of the present application, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present application.

[0026] The following examples are used to illustrate the preparation method of the ultrafine mesophase pitch carbon fiber of the present application.

[0027] Example 1

[0028] Mesophase pitch with a softening point of 293°C and a mesophase content of 91% is used as raw material, and 0.1wt.% carbon nanotubes are added, with a diameter of 20-50 nanometers and a length of 1-5 micrometers; the addition is completed in a molten state of the mesophase pitch with mechanical stirring for 20 minutes (stirring speed is 300 rpm); the precursor is spun by a melt electrospinning process at a spinning temperature of 320°C; the precursor is heated to 240°C in air at a rate of 10°C / min, and then pre-oxidized by uniformly heating from 240°C to 330°C in 3 hours, and then carbonized at 1100°C for 2h under nitrogen protection to obtain ultrafine mesophase pitch carbon fibers with a fiber diameter of 192 nanometers.

[0029] Example 2

[0030] Taking mesophase asphalt with a softening point of 293°C and a mesophase content of 91% as raw material, 0.1wt.% graphene is added, and the length and width of the graphene are 15-25 nanometers; the addition is completed under the molten state of the mesophase asphalt and mechanical stirring for 20 minutes (the stirring speed is 280 rpm); the precursor is spun by melt electrospinning process at a spinning temperature of 323°C; the precursor is heated to 240°C in air at a rate of 10°C / min, and then heated from 240°C to 330°C at a heating rate of 0.5°C / min, and then carbonized at 1100°C for 2h under nitrogen protection to obtain ultrafine mesophase asphalt carbon fiber with a fiber diameter of 201 nanometers.

[0031] Example 3

[0032] Taking mesophase pitch with a softening point of 260°C and a mesophase content of 85% as raw material, 0.1wt.% carbon nanotubes are added, and the diameter of the carbon nanotubes is 30-50 nanometers and the length is 2-5 micrometers; the addition is completed by mechanical stirring for 20 minutes when the mesophase pitch is molten (the stirring speed is 300 rpm); the precursor is spun by melt electrospinning process at a spinning temperature of 295°C; the precursor is heated to 240°C in air at a rate of 10°C / min, and then heated from 240°C to 330°C at a heating rate of 0.5°C / min, and then carbonized at 1100°C for 2h under nitrogen protection to obtain ultrafine mesophase pitch carbon fiber with a fiber diameter of 150 nanometers.

[0033] Example 4

[0034] Taking mesophase asphalt with a softening point of 260°C and a mesophase content of 85% as raw material, 0.2wt.% graphene is added, and the length and width of the graphene are 20-30 nanometers; the addition is completed under the molten state of the mesophase asphalt and mechanical stirring for 20 minutes (the stirring speed is 260 rpm); the precursor is spun by melt electrospinning process at a spinning temperature of 297°C; the precursor is heated to 240°C in air at a rate of 10°C / min, and then heated from 240°C to 330°C at a heating rate of 0.5°C / min, and then carbonized at 1100°C for 2h under nitrogen protection to obtain ultrafine mesophase asphalt carbon fiber with a fiber diameter of 159 nanometers.

[0035] Example 5

[0036] Taking mesophase pitch with a softening point of 320°C and a mesophase content of 95% as raw material, 0.3wt.% carbon nanotubes are added, and the diameter of the carbon nanotubes is 30-50 nanometers and the length is 2-5 microns; the addition is completed by mechanical stirring for 20 minutes when the mesophase pitch is molten (the stirring speed is 300 rpm); the precursor is spun by melt electrospinning process at a spinning temperature of 360°C; the precursor is heated to 240°C in air at a rate of 10°C / min, and then heated from 240°C to 330°C at a heating rate of 0.5°C / min, and then carbonized at 1100°C for 2h under nitrogen protection to obtain ultrafine mesophase pitch carbon fiber with a fiber diameter of 276 nanometers.

[0037] Example 6

[0038] Taking mesophase asphalt with a softening point of 260°C and a mesophase content of 85% as raw material, 0.3wt.% graphene is added, and the length and width of the graphene are 15-25 nanometers; the addition is completed by mechanical stirring for 20 minutes when the mesophase asphalt is molten (the stirring speed is 300 rpm); the precursor is spun by melt electrospinning process at a spinning temperature of 358°C; the precursor is heated to 240°C in air at a rate of 10°C / min, and then heated from 240°C to 330°C at a heating rate of 0.5°C / min, and then carbonized at 1100°C for 2h under nitrogen protection to obtain ultrafine mesophase asphalt carbon fiber with a fiber diameter of 280 nanometers.

[0039] Example 7

[0040] The difference from Example 1 is that the carbon nanotube has a diameter of 65 nanometers and a length of 6.2 micrometers. The experimental results are as follows: the stable spinning time is less than 1 minute, and the diameter has nodules. By comparing Example 7 with Example 1, since the size of the added carbon nanotube is not within the preferred range of the present invention, the spinning continuity is reduced, the diameter is uneven, and the spinning performance and fiber performance are slightly poor.

[0041] Example 8

[0042] The difference from Example 2 is that the graphene diameter is 70 nanometers. By comparing Example 8 with Example 2, since the size of the added graphene is not within the preferred range of the present invention, the spinnability is deteriorated, the fiber has knots, and the spinning performance and fiber performance are slightly poor.

[0043] Example 9

[0044] The difference from Example 1 is that the softening point of the mesophase pitch is 340°C. The experimental results are as follows: the spinning temperature is high, 390°C, and the continuity is poor.

[0045] Comparative Example 1

[0046] The difference from Example 1 is that no carbon nanotubes were added and spinning failed.

[0047] Comparative Example 2

[0048] The difference from Example 1 is that the amount of carbon nanotubes added is 1 wt.%. The experimental results are as follows: the strength of the fiber is affected, and nodules appear in the fiber after graphitization.

[0049] Comparative Example 3

[0050] The difference from Example 1 is that the spinning temperature is 280° C. The experimental results are as follows: the viscosity of the asphalt is high and spinning is impossible.

[0051] It can be seen from the embodiments of the present invention that after adding carbon nanotubes or graphene to the mesophase asphalt, melt electrospinning is used to make nano-scale ultrafine mesophase asphalt carbon fibers, the diameter of which is greatly reduced compared with conventional micron-scale carbon fibers, to obtain a highly oriented mesophase asphalt carbon fiber.

[0052] Obviously, the above embodiments of the present invention are merely examples for clearly explaining the present invention, and are not intended to limit the implementation methods of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is impossible to list all implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are within the spirit scope of the present invention.

Claims

1. A method for preparing mesophase pitch carbon fiber, characterized in that: include: 1) adding 0.1-0.3 wt.% of carbon nanotubes or graphene to molten mesophase pitch to obtain a composite; 2) melt spinning the composite at 295-360° C. using a melt electrospinning process to obtain a raw fiber; 3) The raw silk is pre-oxidized and carbonized to prepare the intermediate phase pitch carbon fiber.

2. The method for preparing mesophase pitch carbon fiber according to claim 1, characterized in that: The softening point of the mesophase asphalt in step 1) is 260-320°C.

3. The method for preparing mesophase pitch carbon fiber according to claim 1, characterized in that: The carbon nanotubes in step 1) have a length of less than 30 nanometers and a diameter of 20-50 nanometers.

4. The method for preparing mesophase pitch carbon fiber according to claim 1, characterized in that: The graphene in step 1) has a length of 15-30 nanometers and a width of 15-30 nanometers.

5. The method for preparing mesophase pitch carbon fiber according to claim 1 or 2, characterized in that: The mesophase asphalt described in step 1) is an asphalt having a mesophase content of more than 85% by volume, preferably more than 90% by volume.

6. The method for preparing mesophase pitch carbon fiber according to claim 1, characterized in that: The adding process of step 1) is carried out under stirring; preferably, the stirring speed is 200-300 rpm and the stirring time is 20-30 minutes.

7. The method for preparing mesophase pitch carbon fiber according to claim 1, characterized in that: The pre-oxidation process in step 3) is to use an oxidant to molecularly cross-link the precursor, the oxidation temperature is 220-330° C., the oxidation time is 2-4 hours, and the oxidant is preferably air.

8. The method for preparing mesophase pitch carbon fiber according to claim 1, characterized in that: The carbonization process in step 3) includes treating at 1000-1300° C. for 0.5-5 hours under nitrogen protection.

9. The method for preparing mesophase pitch carbon fiber according to any one of claims 1 to 8, characterized in that: In steps 1)-3), the softening point of the mesophase pitch is 270-295°C, the addition amount of carbon nanotubes or graphene is 0.15-0.25wt.%, and the spinning temperature is 320-340°C.

10. The mesophase pitch carbon fiber prepared by the above method, wherein the diameter of the mesophase pitch carbon fiber is 150-280 nanometers.

Citation Information

Patent Citations

  • Preparation method of novel mesophase pitch-based composite carbon fibers

    CN104213253A

  • Method for manufacturing high-heat-conduction mesophase pitch-based carbon fibers at low temperature

    CN110983491A

  • Ultrahigh-thermal-conductivity mesophase pitch-based carbon fiber, composite material and preparation method thereof

    CN115029816A

  • Process for producing carbon fibres from mesophase pitch

    GB1496678A

  • Nanofiber-containing pitch-based carbon fiber and method for producing the same

    JP2006307358A